The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1186/1742-4755-10-51
|View full text |Cite
|
Sign up to set email alerts
|

Invest in adolescents and young people: it pays

Abstract: This year’s Women Deliver conference made a strong call for investing in the health and development of adolescents and young people. It highlighted the unique problems faced by adolescent girls and young women–some of the most vulnerable and neglected individuals in the world–and stressed the importance of addressing their needs and rights, not only for their individual benefit, but also to achieve global goals such as reducing maternal mortality and HIV infection.In response to an invitation from the editors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 5 publications
2
35
0
3
Order By: Relevance
“…This can be through availability of tailored sex education programs coupled with appropriate service provision. There are economic and public health costs to not investing in adolescent sexual and reproductive health [31, 32]. Our study results are similar to that of Bankole et al, (2010) which found that access to sexual and reproductive health services including sexual education was still a challenge, worldwide [13].…”
Section: Discussion and Recommendationsupporting
confidence: 86%
“…This can be through availability of tailored sex education programs coupled with appropriate service provision. There are economic and public health costs to not investing in adolescent sexual and reproductive health [31, 32]. Our study results are similar to that of Bankole et al, (2010) which found that access to sexual and reproductive health services including sexual education was still a challenge, worldwide [13].…”
Section: Discussion and Recommendationsupporting
confidence: 86%
“…And adolescentcentered sexual and reproductive health services can prevent health problems and enable adolescents with health problems to get back to good health [9].…”
mentioning
confidence: 99%
“…The findings of small proportion of girls using modern contraceptives, such as birth control pills is surprising given the fact that contraceptives are provided free of charge in SA [Schnieder et al, 1999;Wilkinson et al, 2001;DoH, 2002]. However, this can be explained by (1) the poor knowledge of contraceptives among adolescents in general in SA [Kaufman et al, 2001;Mchunu et al, 2013], and (2) the limited availability of, and access to sexual and reproductive health services targeted at adolescents [Chandra' Mouli et al, 2013;Somba et al, 2014]. Furthermore, the cultural or societal, structural, and individual factors associated with the use of contraceptives are some of the barriers for contraceptive use [Somba et al, 2014;Watts et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses also acknowledged the limited knowledge of their adolescent clients regarding SRH services, as well as the need for more counseling with regards to condom use. Previous research in SSA at large, including SA, has also identified the need for more SRH information and contraceptive knowledge improvement as necessary information adolescents need to be provided with in order for them to make informed decisions regarding their SRH needs [Wood et al, 2006;Holt et al, 2012;Atuyambe et al, 2015;Ochako et al, 2015;Chandra-Mouli et al, 2014;Chandra-Mouli et al, 2013]. Furthermore, nurses emphasized the importance of being sensitive when dealing with their adolescent clients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation